2015
DOI: 10.1007/s00277-015-2395-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy and PGEMOX/GELOX regimen improved prognosis in elderly patients with early-stage extranodal NK/T-cell lymphoma

Abstract: The optimal treatment strategy for elderly patients with natural killer/T-cell lymphoma (NKTCL) remains to be established. A total of 63 elderly patients with newly diagnosed NKTCL were retrospectively reviewed. Among the patients with stage I-II disease, 58.3 % received radiotherapy (RT) ± chemotherapy, and 41.7 % received chemotherapy alone. Compared with chemotherapy alone, RT ± chemotherapy elicited a significantly higher overall response rate (ORR) (100 vs. 57.1 %, P < 0.001) and substantially prolonged 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 26 publications
5
55
1
Order By: Relevance
“…Some experts recently stopped using the standard first-line CHOP in this entity, preferring a more efficient non-multidrug-resistant regimen [2,33]. Among the novel non-multidrug-resistant regimens, those containing asparaginase have elicited promising responses [9][10][11][12][13] even in elderly patients [34], which means that this agent could be considered in CCRT strategies.…”
Section: Discussionmentioning
confidence: 98%
“…Some experts recently stopped using the standard first-line CHOP in this entity, preferring a more efficient non-multidrug-resistant regimen [2,33]. Among the novel non-multidrug-resistant regimens, those containing asparaginase have elicited promising responses [9][10][11][12][13] even in elderly patients [34], which means that this agent could be considered in CCRT strategies.…”
Section: Discussionmentioning
confidence: 98%
“…3,[18][19][20][21][22][23][24] In an analysis of the International Peripheral TCell Lymphoma Project, which retrospectively reviewed the clinical outcomes of 136 patients with …”
Section: Treatment Options Radiotherapy With or Without Chemotherapymentioning
confidence: 99%
“…Our previous studies using a small number of NKTCL cases at a single institution revealed favorable outcomes for children and adolescents but unfavorable prognoses for elderly patients . However, the prognostic significance and treatment outcome of elderly patients with NKTCL have not been established in large, multicenter studies …”
Section: Introductionmentioning
confidence: 99%